1999
DOI: 10.1016/s0883-2927(98)00060-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical trends, palaeorecharge and groundwater ages in the fissured Chalk aquifer of the London and Berkshire Basins, UK

Abstract: The hydrochemical, radiochemical, stable isotope, 14C and dissolved noble gas composition of groundwaters has been determined along two profiles across the confined, fissured Chalk aquifer of the London Basin of southern England, and for selected sites in the adjacent Berkshire Basin. During downgradient flow in the London Basin aquifer, the groundwater chemistry is modified by waterrock interactions: congruent and incongruent reaction of the carbonate lithology resulting in enhanced Mg/Ca and Sr/Ca ratios and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 62 publications
3
57
2
Order By: Relevance
“…This sequence of oxidation±reduction observed is similar to that described in other systems closed to O 2 and which contain organic matter (Edmunds et al, 1984(Edmunds et al, , 1987Kloppmann et al, 1996;Elliot et al, 1999). Despite the lack of Eh measures, it is possible to de®ne a redox boundary coincident with the fall in dissolved O 2 ±NO À 3 content and located in the con®ned aquifer, under the border between the Guadix and Baza Formations.…”
Section: Resultssupporting
confidence: 82%
“…This sequence of oxidation±reduction observed is similar to that described in other systems closed to O 2 and which contain organic matter (Edmunds et al, 1984(Edmunds et al, , 1987Kloppmann et al, 1996;Elliot et al, 1999). Despite the lack of Eh measures, it is possible to de®ne a redox boundary coincident with the fall in dissolved O 2 ±NO À 3 content and located in the con®ned aquifer, under the border between the Guadix and Baza Formations.…”
Section: Resultssupporting
confidence: 82%
“…These values are close to the ocean constant molar ratio (1.5x10 -3 ), suggesting that recharged waters are reflecting the marine aerosol ratio. 8 Consequently, recharge seems to be dominantly affected by the coastal atmospheric deposition along the western part; as towards the east the continental component becomes more prominent. Thus, in Bahia Conception location (Gulf of California), 28 shallow seawater presented higher Br/Cl molar ratio (≈5 x 10 -3 ) due probably to the sink of Cl as result of evaporates precipitation.…”
Section: Cation-anion Concentration and Mineral Solubilitymentioning
confidence: 99%
“…7 The use of physical-chemical hydrogeological approaches in parallel with a wide range of geological settings and field parameters remain a cornerstone in understanding, delineating and defining groundwater flow patterns and in establishing regional flow models. Several studies [8][9][10][11] have shown the positive correlation between groundwater residence time and the concentration of certain major and trace elements as Li. Nevertheless, groundwater age determination remains a challenge when it comes to: the use of plug-flow and binary mixing models, the interpretation of environmental tracers in fractured rocks, the use of radiocarbon in environment dominated by volcanic rocks, and the age sensitivity to vertical heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…As a marine limestone however, Chalk will continue to undergo diagenetic changes, especially where younger influent water comes into contact with older water stored in the Chalk matrix. Groundwater chemistry may thus be modified slowly as it flows through the Chalk, resulting in increases in Mg/Ca and Sr/Ca ratios (Elliot et al, 1999). These ratios are useful in determining water to rock contact times, but because of the heterogeneity of groundwater movement and mixing in the subsurface Variability of dissolved CO 2 in the Pang and Lambourn Chalk river s (Younger and Elliot, 1995), may be difficult to use in estimating groundwater residence times.…”
Section: Dissolved Co 2 In Chalk Streamsmentioning
confidence: 99%